Retrieval performance of quranic texts in jawi and rumi malay scripts - Abdul Wahid, Fauziah; Othman, Roslina (IIUM Press, International Islamic University Malaysia, 2017)
The enhancement in technology has sped the search process making more information available to users in a short amount of time. This also involves semantically enriched data for CLIR, which can either be in the form of different language or different writing system. This book investigated the retrieval performance of Quranic texts translation of Pimpinan Ar-Rahman in Jawi Malay (the old version of Malay Language) and Rumi Malay (the new Roman version of Malay Language) with different version of Malay Language and letter scripting considerations. Methodology implemented was by using queries formulated from FAQs written by Muslim scholars in authenticated printed sources produced in Malaysia. 50 FAQs were selected from Utusan Melayu newspaper for Jawi Malay queries and 50 FAQs from Berita Harian newspaper for Rumi Malay queries. Keyword(s) were derived by authors from FAQs as queries to represent each FAQs. Queries were in Jawi Malay Original, Rumi Malay Transliterated, Rumi Malay Original and Jawi Malay Transliterated.